Apprenticeship as a mode of learning and model of education. Issue 6 (11th July 2016) - Billett, Stephen
Abstract : Purpose: – Apprenticeships are now usually seen as a model of education focused on occupational preparation, albeit manifested in different ways across nation states. However, throughout human history, the majority of occupational preparation has been premised upon apprenticeship as a mode of learning. That is, a preparation arising mainly through apprentices' active and interdependent engagement in their work, rather than being taught or directly guided by more experienced practitioners. The paper aims to discuss these issues. Design/methodology/approach: – A review of literature. Findings: – A way of considering apprenticeship as a mode of learning as well as a model of education. Research limitations/implications: – Three elements of considering and supporting apprenticeship as a mode of learning. Practical implications: – Practice curriculum, practice pedagogies and personal epistemology. Social implications: – A way of considering apprenticeship as a mode of learning as well as a model of education. Originality/value: – A way of considering apprenticeship as a mode of learning as well as a model of education.